2022
DOI: 10.1002/ppul.26144
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic preterm infants suffer from lung function deficits, regardless of bronchopulmonary dysplasia

Abstract: Background The long‐term respiratory consequences for children with bronchopulmonary dysplasia (BPD) are well known. However, there is little emphasis on monitoring preterm infants without BPD. Few studies have explored the lung function status of infants with the symptoms of chronic lung disease of prematurity (CLD). Objective To evaluate functional lung deficits in preterm infants with CLD, and to assess the perinatal determinants of diminished lung function. Methods In our cross‐sectional study, 132 preterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…36 Studies in those born prematurely or at low birthweight show that premature birth, even when uncomplicated by BPD, predicts diminished pulmonary function in later life. 39 Parallel results have been reported using electrical impedance segmentography. 40 Although the focus has naturally been on those patients deemed at highest risk, increasing evidence suggests that even mild degrees of prematurity confer additional risk to long-term lung function.…”
Section: Pulmonary Function Testing Outcomes Of Neonatal Diseasessupporting
confidence: 58%
See 1 more Smart Citation
“…36 Studies in those born prematurely or at low birthweight show that premature birth, even when uncomplicated by BPD, predicts diminished pulmonary function in later life. 39 Parallel results have been reported using electrical impedance segmentography. 40 Although the focus has naturally been on those patients deemed at highest risk, increasing evidence suggests that even mild degrees of prematurity confer additional risk to long-term lung function.…”
Section: Pulmonary Function Testing Outcomes Of Neonatal Diseasessupporting
confidence: 58%
“…This group found that severity factors such as postnatal rescue corticosteroids and the degree of prematurity to predict long‐term impairment of FEF and FEV in adolescents, parallel to the findings in infants 36 . Studies in those born prematurely or at low birthweight show that premature birth, even when uncomplicated by BPD, predicts diminished pulmonary function in later life 39 . Parallel results have been reported using electrical impedance segmentography 40 …”
Section: Pulmonary Function Testing Outcomes Of Neonatal Diseasesmentioning
confidence: 56%